Differences in vertical jump performance between starters and non-starters in professional female volleyball players - Cabarkapa, D.; Cabarkapa, D.; Fry, A. (International Journal of Exercise Science Conference Proceedings, 2024)
As one of the most fundamental skills in volleyball, countermovement vertical jump (CVJ) has been commonly implemented in the applied sports setting as a non-invasive and time-efficient assessment of athletes` lower-body neuromuscular function.